A Low‐Power Low‐Cost 780MHz CMOS FSK Receiver for Short‐Range Wireless Communication. Issue 2 (1st March 2016) - Yin, Yadong; Yang, Yuanting; Zhang, Lihong
Abstract : This paper presents a low‐power low‐cost 780MHz CMOS Frequency shift keying (FSK) receiver for short‐range wireless communication. A current‐reused Low power amplifier (LNA) and a single‐balance passive mixer are employed to cut down the current consumption of the RF frontend in receiver. A 3 rd ‐order active‐RC complex filter with reconfigurable bandwidth is implemented and a novel automatic tuning circuit is used in the filter to eliminate the negative effect of the Process, voltage, temperature (PVT) variations. A novel replica‐circuit master‐slave automatic tuning circuit and a discrete‐time differentiator are employed in demodulator to keep the demodulation performances from the PVT variations and the frequency offset of Intermediate frequency (IF). The receiver is fabricated in 0.18µm CMOS and occupies a chip area of about 0.97mm 2 . It can achieve a sensitivity of −83.7dBm and a tolerance of IF range from 1.5MHz to 3.7MHz with a 4.7mA current consumption under a 1.8V supply.